From sprint to endurance: performance level and pacing profile of international level para-cyclists from C division - Le Toquin, B.; Baconnais, M.; Hamri, I.; Forstmann, N.; Weissland, T.; Toussaint, J.; Schipman, J. (European Journal of Sport Science, 2025)
We investigated how para-cycling sport classes in the C division influence performance levels and pacing profiles in track and road races compared to able-bodied cyclists. For track races, we analyzed data from seven UCI World Para-Cycling Track Championships and UCI World Track Championships (2014-2023) in the male's 1 km time trial and female's 500 m time trial events. Principal component analysis and hierarchical clustering were applied to 125 m splits to identify performance patterns among para-cyclists. For road races, we examined data from individual time trials in 16 UCI World Para-Cycling Cups and Championships (2014-2023) to compare mean speeds and pacing profiles across sport classes. Para-cyclists in the C division performed significantly worse than able-bodied cyclists in both male's 1 km and female's 500 m track time trials (p < 0.05). The analysis revealed a statistically significant variation in performance across sport classes for both track and road events (p < 0.05). However, when comparing adjacent classes, specifically M/WC1-C2 and M/WC3-C4, no significant differences were observed on the track (p > 0.05). Regarding pacing profiles, male MC2 and female WC5 athletes exhibited a pacing pattern characterized by a faster finish (p = 0.01). In the individual time trial, MC3 had a lower mean speed in the second and third laps than in the first lap (p = 0.01), whereas MC4 and MC5 showed no significant mean speed differences across the three laps (p = 0.05). This study demonstrates that performance levels and pacing profiles are sport-class specific and event dependent.